Peningkatan Kapasitas Aparatur Kampung dalam Pengelolaan Dana Desa di Kampung Wasur Distrik Merauke melalui Pendidikan dan Pelatihan - Umiyati Haris; Fransin Kontu; Syahruddin Syahruddin; Hubertus Oja; Kartika Sari; Desi Rachmawati (Universitas Muhammadiyah Manado, 2024)
Improving Capacity building of village officials in the management of the Village Fund is a crucial step to ensure the effective, efficient, and appropriate use of funds. This research was conducted in Wasur Village, Merauke District, through an education and training programme designed to improve knowledge, skills and attitudes of village officials in managing the Village Fund. Methods methods used included a participatory approach by involving the apparatus actively in every stage, from needs identification to post-training evaluation. The results showed in the capacity of the village apparatus, which can be seen from their ability to their ability to develop better budget planning, improve the quality of financial financial reporting, and applying the principles of transparency and accountability in their management of the Village Fund. In addition, there were more positive attitudinal changes towards the importance of good governance in village governance. The discussion emphasised that continuous education and training as well as intensive technical assistance are key factors in maintaining the continuity of sustainability of the capacity building of the apparatus. In conclusion, the programme did not short-term impact but also instils a strong foundation for sustainable development in Wasur Village. It is recommended that similar programmes be held periodically involving various parties to ensure that village officials continue to adapt to the challenges and maintain the quality of Village Fund management for the welfare of the community.